Meta-analysis of the effects of VAR on goals scored and home advantage in football - Rogerson, M.; Knight, D.; Scherer, R.; Jones, B.; McManus, C.; Waterworth, S.; Murray, K.; Hope, E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Video assistant referee (VAR) has been introduced to elite football (soccer) to avoid clear and obvious mistakes, especially for goal scoring situations. Some literature has reported on VAR`s impact on the game across particular league competitions. The current study meta-analysed data across two seasons (pre-VAR and post-VAR) from 20 competitions (n = 9076 matches; men`s domestic leagues and both men`s and women`s international tournaments) to examine the overall impact that VAR initially had on number of goals scored, and the extent of inter-competition heterogeneity. A secondary aim was to determine any VAR-associated reduction in home advantage for goals scored, mean result direction and match closeness. Findings demonstrated that there were no overall statistically significant nor meaningful differences between pre and post-VAR seasons/competitions for total number of goals scored per match. Similarly, there were no VAR-associated reductions in home advantage in terms of goals scored, mean result direction and closeness of match outcome. There was moderate heterogeneity for some comparisons, and VAR lessened inter-competition variance for number of goals scored and match score closeness. Implications of findings are discussed. As the largest VAR-focused study and the first to use meta-analytic approach, the current findings are the most comprehensive and definitive to date.